A systematic review of eculizumab for atypical haemolytic uraemic syndrome (aHUS). Issue 11 (4th November 2013) - Rathbone, John; Kaltenthaler, Eva; Richards, Anna; Tappenden, Paul; Bessey, Alice; Cantrell, Anna
Abstract : Objective: To determine the efficacy and safety of eculizumab for patients with atypical haemolytic uraemic syndrome (aHUS), compared with current treatment options. Design: A systematic review was performed according to the general principles of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement. All study designs were included, except case histories. Participants: All patients diagnosed with aHUS were included; no age restrictions were used. Interventions: Eculizumab compared with current treatment options. Identification of studies: 12 databases were searched. Additional searches were performed through the Food and Drug Administration (FDA) and the Electronic Medicines Compendium websites, Google internet searches and contacting clinical experts. Reference lists of relevant articles were checked for additional studies. Results: 2 small, uncontrolled prospective multinational, multicentre studies and one small uncontrolled multinational, multicentre retrospective study were included. No meta-analyses were performed. Compared with baseline measures, thrombotic microangiopathy event-free status was achieved in 84% of patients in the prospective studies. Adverse events, as documented by enrolling investigators were frequent, with upper-respiratory tract infection affecting a third of patients. No deaths or episodes of meningitis or meningococcal septicaemia occurred in the prospective studies. Results of the study extension phases up to 114 weeks indicate that the benefits of the treatment are sustained. Conclusions: Eculizumab is clinically effective for the treatment of aHUS. Further research is needed to evaluate eculizumab, ideally using patient-related clinical outcomes. If randomised studies are not feasible, study investigators should ensure that the threat of bias is minimised in future studies of eculizumab with respect to the reporting of patient recruitment and selection.